2020
DOI: 10.1093/ofid/ofaa338
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Metformin in Nondiabetic People With HIV: Influence on Weight and Gut Microbiota

Abstract: Background People living with HIV (PLWH) taking antiretroviral therapy (ART) may experience weight gain, dyslipidemia, increased risk of non-AIDS comorbidities and long-term alteration of the gut microbiota. Both low CD4/CD8 ratio and chronic inflammation have been associated with changes in the gut microbiota of PLWH. The anti-diabetic drug metformin has been shown to improve gut microbiota composition while decreasing weight and inflammation in diabetes and polycystic ovary syndrome. Nevert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 82 publications
(71 reference statements)
3
32
0
Order By: Relevance
“…We conducted a prospective study to examine the effect of metformin on body weight in non-diabetic, non-obese people living with HIV and receiving effective antiretroviral therapy (ART). We showed that metformin, independent of its glucoselowering effect, increased plasma levels of GDF-15 and decreased weight, and its effects vanished upon discontinuation, establishing a direct cause-effect relationship between GDF-15 plasma level change and weight change during and after metformin discontinuation (25). Although the mechanism responsible for metformin-induced GDF-15 expression is not yet deciphered, several pathways have been described to induce GDF-15 expression.…”
Section: Metformin Induces Gdf-15 Via Atf4 and Chopmentioning
confidence: 79%
See 2 more Smart Citations
“…We conducted a prospective study to examine the effect of metformin on body weight in non-diabetic, non-obese people living with HIV and receiving effective antiretroviral therapy (ART). We showed that metformin, independent of its glucoselowering effect, increased plasma levels of GDF-15 and decreased weight, and its effects vanished upon discontinuation, establishing a direct cause-effect relationship between GDF-15 plasma level change and weight change during and after metformin discontinuation (25). Although the mechanism responsible for metformin-induced GDF-15 expression is not yet deciphered, several pathways have been described to induce GDF-15 expression.…”
Section: Metformin Induces Gdf-15 Via Atf4 and Chopmentioning
confidence: 79%
“…However, a meta-analysis showed that metformin contributed to a decrease of body mass index (BMI) and waist to hip ratio (WHR) in 11 and 7 RCTs of PCOS women respectively, compared to placebo (75). Finally, a 12-week metformin treatment decreased the weight of nondiabetic people living with HIV under antiretroviral therapy (25).…”
Section: Metformin Decreases Body Weight In Diabetic and Non-diabeticmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced production of cytokines such as TNF-α and IL-6 was seen in metformin-treated patients ( 79 ). Furthermore, metformin may also reduce inflammation by altering the composition of gut microbiota ( 80 , 81 ). A retrospective cohort study on PLWH with diabetes mellitus showed that Metformin use was associated with improved CD4 recovery ( 82 ).…”
Section: Hyper-inflammation In Hiv Infection and Covid-19mentioning
confidence: 99%
“… 7 , 40 , 41 In relatively healthy individuals, the levels of GDF15 rise with age, intense exercise, obesity, smoking, pregnancy, and use of metformin. 42 - 45 GDF15 is expressed in higher concentrations in the placenta and prostate and is released in homeostatic conditions in smaller amounts by other tissues such as the liver, colon, stomach, heart, lungs, bladder, and kidneys. Conversely, higher levels are released by tissue damage and stress creating a peripheral non-homeostatic regulation of neural circuitry.…”
Section: Contribution Of Gdf15 To Anorexia and Cachexiamentioning
confidence: 99%